CGIAR Collaborative Platform on Gender Research - Communities of Practice - CGIAR Collaborative Platform on Gender Research (CGIAR Collaborative Platform on Gender Research, 2017)
This presentation was given at the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.